Математичне моделювання нестаціонарних режимів роботи перемотувальної машини відкритого типу - Висоцька, Христина (КІНПАТРІ ЛТД, 2013)
The results of mathematical modeling of starting processes open typere winding machine, which includes an asynchronous engine, spongy and pass transmissions, anchorman and slave drums with fabric and intermediate rollers, are examined. The calculation of non-stationary modes is executed by compatible integration of equalizations of the electromagnetic phenomena in an engine and equalizations of motion of the mechanical system. The influence of transmission relations of mechanical transmissions, inertia descriptions of scrolls of drums and rollers, coefficients of inflexibility branches of fabric and also coefficients of slave drum on effort in the branches of fabric, is analyzed.
Mathematical modeling of non-stationary modes of operations of open typere winding machine